Generalized Correlation for the Physical and Psychometric Properties of Chlorodifluromethane - Ismail, Natheer Nori (Journal of Petroleum Research and Studies, 2013)
Chlorodifluoromethane is used as pure or in mixture for refrigeration (medium-high temperatures). It is also used as a blowing agent for extruded polystyrene and polyurethane foams and a component in sterilant gas mixtures. A new generalized correlation for the physical and psychometric properties of liquid Chlorodifluromethane as a function to temperature are introduced, Equation (1). The new correlation was statistically compared with those previously presented and found to be : … (1) Where : A, B, C and D are the property constants, T is the temperature in degrees centigrade.